A high-performance porous flexible composite film sensor for tension monitoring. Issue 40 (15th September 2022) - Feng, Yuanyuan; Cai, Rui; Zhou, Yi; Hu, Zonghao; Wang, Yanlong; Liu, Daiqiang; Han, Sensen; Zhao, Jiankai; Xu, Lisheng; Meng, Qingshi
Abstract : A high-performance porous flexible composite film sensor for tension monitoring. The sensor can monitor the strain of the whole field and then use contour maps to locate damage. Abstract : Flexible, lightweight sensors with a wide strain-sensing range are showing increasing significance in structural health monitoring compared with conventional hard sensors, which typically have a small strain range, are heavyweight, and have a large volume. In this work, salt particle precipitation and mechanical coating methods are used to fabricate porous graphene nanoplatelet (GNP)/polydimethylsiloxane (PDMS) flexible sensors for tension monitoring in structural health applications. The signal transformation through the Back Propagation (BP) algorithm is integrated to provide monitoring data that are comparable with other sensors. The results reveal that the flexible sensors with a low content of GNPs (0.1–0.25 wt%) possess better flexibility, allowing tensile strains over 200% to be measured. In addition, due to the enhanced deformation capacity of the pore structures, they can achieve high sensitivity (1–1000) under 65% strain, and a fast response time (70 ms) under 10% strain at 60 mm min −1 . They also show high performance in the fatigue test (20 000 cycles) under 5% strain, and can effectively respond to bending and torsion. In addition, the sensors show an obvious response to temperature. Overall, the prepared flexible composite sensors in this work have the advantages of a wide strain-sensing range, a full-coverage conductive network, and being lightweight, and show potential for structural health monitoring in the near future.